// End script hiding -->

There are two ways to do this: First way: Let the roots be +r and -r Then x² - kx + 8 = 0 whould have to factor as (x - r)(x + r) = 0 which multiplies out to x² + rx - rx + r² = 0 x² + r² = 0 So since the terms in x cancel, the coefficient of r must be zero, which makes k = 0. However the roots are imaginary since r² must equal to 8 x² + 8 = 0 x² = -8 __ x = ±Ö-8 ___ x = ± iÖ4*2 _ x = ±2iÖ2 ------------------------ The other way to do it is to use the quadratic formula: x² - kx + 8 = 0 The two roots are and Setting one equal to the negative or the other: Multiply through by 2 Subtracting the radical from both sides: k = -k 2k = 0 k = 0 And the two roots are Edwin